Penerapan Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) untuk Meningkatkan Pemahaman Konsep Siswa Kelas VIII Sekolah ABC Topik Relasi dan Fungsi [The Implementation of the Student Team Achievement Division (STAD) Cooperative Learning Type to Improve Conceptual Understanding of Relation and Function Topics of Grade VIII Students at ABC School] - Debima Solli Ruruk Tipa; Maya Puspitasari Izaak; Oce Datu Appulembang (Universitas Pelita Harapan, 2016)
This research was based on the observation that most of the students had low conceptual understanding. The Student Team Achievement Division (STAD) Cooperative Learning type was applied. The purpose of the research was to increase conceptual understanding through the implementation of STAD and to understand the procedures of STAD Cooperative Learning in increasing conceptual understanding. This was the Classroom Action Research (CAR) model by Kemmis and Taggart that was conducted between August 3, 2015 and September 21, 2015 at the Grade VIII ABC School. There were three cycles of CAR that involved 32 students. The instruments of data collection were a test paper, a group assignment sheet, an open-ended observation sheet, a questionnaire, a mentor feedback sheet, a mentor and a student interview sheet, and reflection journals. Based on the data analysis, it was found that the implementation of STAD Cooperative Learning was able to increase the conceptual understanding of Grade VIII students on the topics of Relation and Function. BAHASA INDONESIA ABSTRAK: Penelitian ini didasarkan atas hasil observasi yang menemukan bahwa sebagian besar siswa memiliki pemahaman konsep yang rendah.Pembelajaran kooperatif tipe STAD (Student Team Achievement Division) dicoba untuk diterapkan. Penerapan STAD diharapkan dapat mencapai tujuan penelitian yaitu meningkatkan pemahaman konsep melalui penerapan STAD dan mengetahui langkah-langkah pembelajaran kooperatif tipe STAD dalam meningkatkan pemahaman konsep. Penelitian ini adalah penelitian tindakan kelas (PTK) dengan model Kemmis dan Taggart yang berlangsung selama 03 Agustus 2015 - 21 September 2015 di kelas VIII di sekolah ABC. Penelitian dilakukan dengan tiga siklus dengan melibatkan 32 siswa. Adapun instrumen yang digunakan dalam pengumpulan data yaitu lembar tes, lembar LKK kelompok, lembar observasi terbuka, lembar angket, lembar umpan balik mentor, lembar wawancara siswa dan mentor, dan jurnal refleksi. Berdasarkan analisis data, diperoleh bahwa penerapan tahapan pembelajaran kooperatif tipe STAD (Student Team Achievement Division) mampu meningkatkan pemahaman konsep siswa kelas VIII pada topik relasi dan fungsi.